GOVERNMENT INTERVENTION TO THE MARKET FAILURES AND GOVERNMENT FAILURES IN THE ENERGY SECTOR (Third Sector Social Economic Review, 2022)
In this study; market failures in the energy market which carry production and provision of the energy as a public good, the tools of the governments to prevent those failures, and the government failures that are possible in the market with increasing involvement of governments, are examined systematically. By adopting the normative analysis method, the relationships of each type of failure with the energy market and energy as a public good, are investigated. Consequently, a discussion on the reasons for market failures and government failures generated by the private sector or the nature of the energy as a commodity or a public good and the ways to avoid those failures tried to be put forward and some policy offers are provided. A sufficient number of private sector actors which may enable the competition and the government as a strong check – balance component, should take their places in an ideal structure. However, even in this case there is no guarantee to prevent mentioned market failures or government failures. Because of those problems,  legal foundations should be improved, the sanctions against market distortive actions must be empowered and government failures must be kept under control by the surveillance systems. As the conclusion, eliminating the market failures and government failures would be possible by the actions of the government itself as the legal – structural regulations and existance of sanctions with the binding clauses.
Keywords: Energy Markets; Market Failures; Government Failures; Government Intervention Tools; Legal Regulations